Estimation of the effects of climate change on flood-triggered economic losses in Japan - Tezuka, S.; Takiguchi, H.; Kazama, S.; Sato, A.; Kawagoe, S.; Sarukkalige, Priyantha Ranjan (Elsevier BV, 2014)
This study evaluates the effects of climate change on economic losses due to flood-related damage in Japan. Three selected GCM climate data were downscaled using an analytical method that uses observed precipitation data as the reference resolution. The downscaled climate data were used to estimate extreme rainfall for different return periods. The extreme rainfall estimates were then entered into a two-dimensional (2D) non-uniform flow model to estimate flood inundation information. A technique based on the land use type of the flood area was employed to estimate economic losses due to flood damages. The results of the rainfall analysis show that at present (in 2000), the Nankai region, and the area from Wakayama Prefecture to Kagoshima Prefecture and the mountains of the Japan Alps receive very high extreme rainfall. By 2050, in addition to these areas, the rainfall in the Tokai and Koshinetsu regions will be 1.2 to 1.3 times greater than at present. The overall variations show that the potential economic loss is greater for the SRES-B1, A2 and A1B scenarios for all return periods. These results clearly show that flood-related economic losses in Japan will increase significantly in the future as a result of climate change. It indicates that Japan needs to increase the capital investment to implement flood control and mitigation measures in the future. As this study presents comprehensive results in very fine resolution (1 km×1 km), the outcome of this study is more important for regional scale decision making processes will be useful to the public, economists, and policy and decision makers in planning and designing flood control measures.